FROM HASHTAGS TO CLASSROOMS: SOCIAL MEDIA AS A CATALYST FOR EDUCATIONAL TRANSFORMATION - K. Jasmine; K. M. Keerthika (International Journal of Research -GRANTHAALAYAH, 2026)
The growing influence of social media has redefined how young people communicate, learn, and express themselves. This paper explores social media’s role as a transformative educational tool within the framework of India’s National Education Policy (NEP) 2020. It examines how digital platforms such as YouTube, Instagram, and X (formerly Twitter) promote participatory learning, collaborative communication, and multilingual engagement among students. At the same time, the paper acknowledges the challenges of overexposure, digital distraction, and the erosion of authentic communication in the learning environment. Drawing parallels from Dave Eggers’ the Circle, which critiques society’s increasing dependence on digital transparency and constant connectivity, the study highlights the need for digital ethics and media literacy in education. The analysis situates social media not merely as a space for entertainment but as a catalyst for inclusive, accessible, and student-centered learning experiences. By integrating literature with educational theory, the paper argues that responsible social media use can advance NEP 2020’s vision of equitable and technology-driven education. Ultimately, it calls for a balanced digital pedagogy that empowers youth to think critically, communicate effectively, and navigate the evolving relationship between technology, language, and education.